GDF11 rapidly increases lipid accumulation in liver cancer cells through ALK5-dependent signaling - Frohlich, Jan; Mazza, Tommaso; Sobolewski, Cyril; Foti, Michelangelo; Vinciguerra, Manlio (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2021)
Hepatocellular carcinoma (HCC) is one of the fastest-growing causes of cancer-related mortalities worldwide and this trend is mimicked by the surge of non-alcoholic fatty liver disease (NAFLD). Altered hepatic lipid metabolism promotes HCC development through inflammation and activation of oncogenes. GDF11 is a member of the TGF-β superfamily and recent data have implicated GDF11 as an anti-aging factor that can alleviate high-fat diet induced obesity, hyperglycemia, insulin resistance and NAFLD. However, its role in hepatic lipid metabolism is still not fully delineated. The aim of the present study was to characterize the role of GDF11 in hepatic and HCC cells lipid accumulation. To achieve this, we performed imaging, biochemical, lipidomic, and transcriptomic analyses in primary hepatocytes and in HCC cells treated with GDF11 to study the GDF11-activated signaling pathways. GDF11 treatment rapidly triggered ALK5-dependent SMAD2/3 nuclear translocation and elevated lipid droplets in HCC cells, but not in primary hepatocytes. In HCC cells, ALK5 inhibition hampered GDF11-mediated SMAD2/3 signaling and attenuated lipid accumulation. Using ultra-high-performance liquid chromatography/mass spectrometry, we detected increased accumulation of longer acyl-chain di/tri-acylglycerols and glycerophospholipids. Unbiased transcriptomic analysis identified TGF-β and PI3K-AKT signaling among the top pathways/cellular processes activated in GDF11 treated HCC cells. In summary, GDF11 supplementation promotes pro-lipogenic gene expression and lipid accumulation in HCC cells. Integration of our "omics" data pointed to a GDF11-induced upregulation of de novo lipogenesis through activation of ALK5/SMAD2/3/PI3K-AKT pathways. Thus, GDF11 could contribute to metabolic reprogramming and dysregulation of lipid metabolism in HCC cells, without effects on healthy hepatocytes.
Keywords: hepatocyty; lipogeneze; Cell Line, Tumor; hepatocelulární karcinom; Up-Regulation; protein Smad2; lidé; kostní morfogenetické proteiny; nádory jater; Carcinoma, Hepatocellular; Lipid Metabolism; upregulace; signální transdukce; Signal Transduction; Growth Differentiation Factors; metabolismus lipidů; Hepatocytes; Smad2 Protein; Bone Morphogenetic Proteins; Liver Neoplasms; Lipogenesis; Receptor, Transforming Growth Factor-beta Type I; TGF-beta receptor I. typu; nádorové buněčné linie; růstové diferenciační faktory; Humans